Videofluoroscopic swallow study features of lower esophageal sphincter achalasia‐like syndrome in dogs - Megan E. Grobman; James Schachtel; C. Prakash Gyawali; Teresa E. Lever; Carol R. Reinero (Journal of Veterinary Internal Medicine, 2019)
Abstract Background Megaesophagus (ME) carries a poor long‐term prognosis in dogs. In people, lower esophageal sphincter (LES) disorders causing functional obstruction are rare causes of ME that may respond to targeted treatment. Functional LES disorders are reported rarely in dogs because of challenges in diagnostic methodologies. Hypothesis/Objectives To identify dogs with videofluoroscopic swallow study (VFSS) features of LES achalasia‐like syndrome (LES‐AS). We hypothesized that dogs with LES‐AS could be distinguished from normal dogs using standardized VFSS criteria. Animals Dogs with LES‐AS by VFSS (n = 19), healthy normal dogs (n = 20). Methods Retrospective study. One‐hundred thirty dogs presented to the University of Missouri Veterinary Health Center (MU‐VHC) between April 2015 and December 2017 for a free‐feeding VFSS; 20 healthy dogs were included as controls. Swallow studies were evaluated for failure of the LES to relax during pharyngeal swallow (LES‐AS). Affected dogs subsequently were evaluated using standardized criteria to identify metrics important for identifying and characterizing dogs with LES‐AS. Results Nineteen dogs with LES‐AS were identified out of 130 VFSS. Megaesophagus was present in 14 of 19 (73.7%) dogs with LES‐AS. A baseline esophageal fluid‐line and “bird beak” were present in 68.4% (95% confidence interval [CI], 47.5%‐89.3%) and 63.2% (95% CI, 41.5%‐84.8%) of affected dogs, respectively. The esophagus was graded as acontractile (8/19), hypomotile (8/19), or hypermotile (3/19). Conclusions and Clinical Importance Dogs with LES‐AS may successfully be identified by VFSS using a free‐feeding protocol. These data are of critical clinical importance because a subpopulation of dogs with functional LES obstruction may be candidates for targeted intervention.